THE INFLUENCE OF ROLE AMBIGUITY AND PROFESSIONAL SKEPTICISM ON INTERNAL AUDIT EFFECTIVENESS THROUGH INDEPENDENCE - Febriati Rusyda D. Sagala; Rita Anugerah; Andreas; Ria Nelly Sari; M. Rasuli (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The Influence of Role Ambiguity and Professional Skepticism on Internal Audit Effectiveness Through Independence, supervised by Prof. Dr. Rita Anugerah, SE, MAFIS, Ak, CA and Prof. Dr. Andreas, SE, MM, Ak, CPA, CA. This research aims to determine the influence of role ambiguity and professional skepticism on internal audit effectiveness through independence as mediation. The population in this study was all 57 Internal Auditors in the Regional Inspectorate of Riau Province, consisting of 35 men and 22 women. This research uses Warp PLS 07. The research results show that Role Ambiguity has no effect on Independence with a significant p value <0.059. Role ambiguity has a positive effect on internal audit effectiveness of 0.278 with a p value of 0.014. Skepticism has a positive effect on independence of 0.430 with a p value of <0.001. The Skepticism variable has no effect on the effectiveness of internal audit with a significance value of 0.430. The independence variable has a direct positive effect on internal audit effectiveness of 0.731 with a p value of <0.001. The results of the mediation test show that Independence does not mediate between Role Ambiguity and Internal Audit Effectiveness, Skepticism influences Internal Audit Effectiveness through Independence as mediation. The results of the interviews conducted are in line with this research so that they can strengthen the results of this research.